The Relationship Between Breast Volume and Thoracic Kyphosis Angle - Ertem, Şenay Bengin; Malçok, Ümit Ali (European Journal of Therapeutics, 2023)
Objective: It has been hypothesized that a disproportionate upper body weight caused by macromastia places abnormal stress on the spine, which may lead to skeletal abnormalities. To evaluate whether there is a relationship between breast volume and the thoracic kyphosis angle measured on thorax CT images. Methods: A total of 448 female patients who underwent thoracic CT examinations were included in this study. Breast volume [ml], by using the "organ segmentation method"; thoracic kyphosis angles by using Cobb's method were made manually on the workstation. Results: Mean right breast volume was 902.03 ± 376.47 (154.21 - 2366.20 ml), left breast volume was 911.01 ± 383.34 (167.93 - 2894.07 ml), total breast volume was 1810.09 ± 750.82 (354.39 - 5100.68 ml). The total breast volume (p<0.001) and thoracic kyphosis angle (p=0.012)in patients aged 50-69 years were significantly higher than those aged 17-29 years. Larger total breast volume [p<0.001] and thoracic kyphosis angle (p<0.001) values were associated with larger BMI intervals. A significant positive correlation was observed between the total breast volume and thoracic kyphosis angle (r=0.771, p<0.001). Conclusion: Our results showed that the thoracic kyphosis angle significantly increased in parallel with a larger total breast volume, and that total breast volume was an independent risk factor for thoracic kyphosis angle. The manual organ segmentation method we used was found to be reliable and easy to apply, but time-consuming technique for calculating BV.